Adjuvant Sorafenib Following Radiofrequency Ablation for Early-Stage Recurrent Hepatocellular Carcinoma With Microvascular Invasion at the Initial Hepatectomy - Wei, Meng-Chao; Zhang, Yao-Jun; Chen, Min-Shan; Chen, Yong; Lau, Wan-Yee; Peng, Zhen-Wei (Frontiers in Oncology, 2022)
Background: The efficacy of radiofrequency ablation (RFA) for early-stage recurrent hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI) at the initial hepatectomy is limited. Our study aimed to explore whether adjuvant sorafenib following RFA could improve the situation. Methods: We retrospectively included 211 early-stage (tumor number ≤3 and tumor size 2-5cm) recurrent HCC patients with MVI at the initial hepatectomy who underwent adjuvant sorafenib following RFA or RFA alone in 13 centers from June 2013 to June 2020. In the combination group, sorafenib 400mg twice daily was administered within 7 days after RFA. Overall survival (OS) and recurrence-free survival (RFS) were compared. Subgroup analysis based on MVI grade was performed. Results: 103 patients received the combination therapy and 108 patients received RFA alone. The combination therapy provided better survival than RFA alone (median RFS: 17.7 vs 13.1 months, P <0.001; median OS: 32.0 vs 25.0 months, P =0.002). Multivariable analysis revealed that treatment allocation was an independent prognostic factor. On subgroup analysis, the combination therapy provided better survival than RFA alone in patients with M1 along with either a tumor size of 3-5cm, tumor number of 2-3 or alpha-fetoprotein (AFP) >400μg/L, and in those with M2 along with either a tumor size of 2-3cm, 1 recurrent tumor or AFP ≤400μg/L. Conclusions: Adjuvant sorafenib following RFA was associated with better survival than RFA alone in early-stage recurrent HCC patients with MVI at the initial hepatectomy. Besides, MVI grade could guide the application of adjuvant sorafenib.